PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PDAM TIRTA TUAH BENUA KUTAI TIMUR - Mardiana, Wuryastuti, Titin Ruliana (EKONOMIA, 2015)
The main objective of this study was to determine the influence of working environment and work motivation on employees job satisfaction PDAM Tirta Tuah BenuaEast Kutai. The noun collected through questionnaires and conducted on 110 employees of PDAM Tirta Tuah Benua East Kutai periode of 2013. Analysis of the datain this study using SPSS version 16.0, the sampling technique used was simple random sampling and testing technique of noun used in this research include testing the validity of the factor analysis, the cronbachalpha reliability test with multiple linier regression analysis, to test and prove the research hypothesis.Analysis result showed that the count results helping by SPSS 16,0 Concluded that Fhit = 10,2 with 0,000 significant. Work miliew (X1) positive effect significant with work satisfied of PDAM Tirta Tuah Benua East Kutai worker. Work motivation (X) positive effect significant with work satisfied of PDAM Tirta Tuah Benua East Kutai worker. Work miliew (X1) and Work Motivation (X2) effect significant with work satisfied of PDAM Tirta Tuah Benua East Kutai.Hypothesis shows that H1 = Work Environment significant posititive effect on employee job satisfaction of PDAM Tirta Tuah Benua East Kutai.H2 = Work Motivation significant positive effect on employees job satisfaction of PDAM Tirta Tuah Benua East Kutai.H3 = Working Environment significant positive effect on employee job satisfaction of PDAM Tirta Tuah Benua East Kutai.Test sig t greater at 5% then there heterokedastisitas.Value F arithmatic performance of employees is greater than the F table ( 4,42) so that Ho is rejected and Ha be accepted.If significant level below 0,05 then the hypothesis be accepted.If level significanly greater than 0,05 then the hypothesis is rejected.Based on the anlysis,the authors provide suggestions for further research are expected to be examined by other variables beyond the variables that have been investigated in order to obtain a more varied results that can affect the job saticfaction of employees.